Sources on the History of Ethnic Entrepreneurship of the Republic of Adygea and the Black Sea in the Early 1990s - M. V. Belozerova (Научный диалог)
The necessity of expanding the corpus of sources is substantiated when analyzing the processes of forming entrepreneurship in the early 1990s among ethnic groups of the Adygei of the Republic of Adygea and the Black Sea coast of the Caucasus (Shapsugs). The study is based on archival materials (State treasury institution of the Republic of Adygea “National Archive of the Republic of Adygea”), acts of federal law, media publications (“Kommersant Power”), and interviews of representatives of the Shapsug community. The main attention was paid to identifying general trends and regional specifics of privatization of municipal and state property, and the creation of private enterprises. Based on the analysis of archival documents and determination of their informative capacity, it is shown that, in general, the privatization of municipal enterprises and agricultural facilities took place in accordance with Russian federal legislation. Based on a comparative analysis of all the involved sources, their informative capacity was determined, the specifics of privatization of large state enterprises (lack of decisions of federal departments) and agricultural enterprises on the Black Sea coast without land privatization were revealed. It is concluded that privatization, having laid the foundation for the formation of ethnic entrepreneurship and the layer of entrepreneurs, did not contribute to the achievement of other tasks in mono-and multi-ethnic enclaves: improving the efficiency of enterprises, social development of regions and social protection of the population.